Photorespiration mutants of Arabidopsis thaliana deficient in serine-glyoxylate aminotransferase activity - Somerville, C. R. (1980)
Three mutants of the crucifer Arabidopsis thaliana (Linnaeus) Heynhold were isolated that are completely lacking in activity catalyzed by serine-glyoxylate aminotransferase (EC 2.6.1.45), a peroxisomal enzyme involved in photorespiratory carbon metabolism. These mutants were viable and exhibited normal photosynthesis under conditions that suppressed photorespiration, but they were inviable and photosynthesized at greatly reduced rates under conditions that promoted photorespiration. Serine and glycine accumulated as end products of photosynthesis in the mutants, mostly at the expense of starch and sucrose. The mutants are allelic, and the segregation patterns of plant viability, photosynthetic activity, and enzyme activity in the F(1) and F(2) generations indicated that all the observed effects were caused by a single recessive nuclear mutation. This conclusion was confirmed by the isolation of seven revertants in which viability, photosynthetic capacity, and enzyme activity were simultaneously restored. Mutants of the type described here, in which photorespiration is changed from a merely wasteful process into one that is lethal, may permit the direct selection of secondary mutations that reduce photorespiration.